Trauma-induced coagulopathy: Incidence and outcome in patients with isolated traumatic brain injury in a level I trauma care center in India - Rani, Poonam; Panda, Nidhi; Hazarika, Amarjyoti; Ahluwalia, Jasmina; Chhabra, Rajesh (Asian Journal of Neurosurgery, 2019)
Context: Trauma-induced coagulopathy (TIC) is life-threatening in head injury patients, and there is a lack of Indian data on its incidence and outcome. Aims: In this study, incidence and outcome related to coagulopathy were assessed in patients with moderate-to-severe isolated traumatic brain injury (iTBI). Settings and Design: A prospective observational study carried out in patients admitted within 24 h of injury. Materials and Methods: One hundred patients with moderate-to-severe iTBI were included. Samples for coagulation tests (prothrombin time [PT], PT index [PTI], international normalization ratio [INR], activated partial thromboplastin time, and platelet count) were collected at 5 points of time for 72 h. TIC was diagnosed if any three readings were abnormal during this period. Patients were also followed up posthospital discharge using the Glasgow Outcome Score (GOS) at 1 and 3 months. Statistical Analysis: Data were analyzed using SPSS ver. 21. Logistic regression analysis was employed to determine individual coagulation test as best predictors for mortality. P < 0.05 was considered statistically significant. Results: The incidence of TIC was found to be 62%; it was 63.75% in severe head injury and 55% in moderate head injury patients. Deranged INR at the time of hospital admission (odds ratio [OR] 4.38) and PTI at 24 h (OR 3.913) are highly predictive of mortality. There was no significant difference in GOS score at 1 and 3 months. Conclusions: The incidence of TIC in our study was 62% among iTBI patients. It contributes to increased mortality at 1 and 3 months. However, the neurological outcome was not different in between the groups.
Keywords: Coagulopathy; GOS; isolated head injury